(untitled) (PJDOL, 2023)
In 21th Distance mode of learning plays significant role in the promotion of education. By the help of distance mode of learning we educate those who lives far away from us, through distance mode learning we educate them. The key purpose of the current investigation was to examine the perception of female students towards the promotion of distance mode learning in Pakistan.